2007
DOI: 10.1590/s0102-86502007000100012
|View full text |Cite
|
Sign up to set email alerts
|

1.8 cineole decreases gastric compliance in anesthetized rats

Abstract: PURPOSE: To study the effect of 1,8 cineoleee components of the essencial oil of Croton nepetaefolius - plant of North-East of Brasil, used in the popular medicine for riots of the gastrointestinal tract - on the motor behavior of the gut of Wistar rats. METHODS: Used 16 male animals under jejun of 24h weighing 300-350g. The effect of 1.8 cineoleee (1 or 3mg/Kg) on gastric compliance had been lead in anaesthetized rats. The variations of the gastric volume (GV), had been measured by plethysmography, while AP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…We found that inhalation of 1,8-cineole and eucalyptus significantly decreased SBP due to the anxiolytic effect of 1,8-cineole, but the differences between groups were not significant. 1,8-Cineole administration has also been shown to reduce gastric compliance, arterial pressure, and cardiac frequency in anesthetized rats [27]. Furthermore, a high dose (10 mg/kg) of 1,8-cineole was associated with hypotension and bradycardia in both anesthetized and conscious rats [20].…”
Section: Discussionmentioning
confidence: 99%
“…We found that inhalation of 1,8-cineole and eucalyptus significantly decreased SBP due to the anxiolytic effect of 1,8-cineole, but the differences between groups were not significant. 1,8-Cineole administration has also been shown to reduce gastric compliance, arterial pressure, and cardiac frequency in anesthetized rats [27]. Furthermore, a high dose (10 mg/kg) of 1,8-cineole was associated with hypotension and bradycardia in both anesthetized and conscious rats [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that intravenous injection with the essential oil of C. zehntneri or nepetaefolius could induce rapid and dose-dependent hypotension and bradycardia [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It is considered an unwanted invasive species in Zapata Swamp, Matanzas-Cuba, causing losses to plant biodiversity. Its essential oils have been evaluated and interesting effects were found, such as anti-inflammatory (Neves et al, 2007), antimalarial (Fernández-Calienes et al, 2008), bactericidal and fungicidal (Pino et al, 2011), larvicidal and repellent (Amer and Mehlhorn, 2006;Leyva et al, 2012). Nevertheless, only a few studies have reported the efficacy of this plant against nematodes.…”
Section: Introductionmentioning
confidence: 99%